PENGARUH TEMPERATUR TERHADAPNKOMPOSISI KARBON PADA PROSES REDUKSI OKSIGEN HASIL KARBONISASI TEMPURUNG KELAPA - widitama, aris kusnul; masruroh, masruroh; nuriyah, nur lailatin (Department of Physics - Faculty of Science, 2013)
The reduction process for oxygen in the carbon content using hydrogen has been observed. The carbon was obtained from carbonization of coconut shells by simple heating method at the temperature of 600oC and heating rate of 6.55oC/min. The composition of carbon were analyzed without reducion process and after one by EDAX. The composition before reduction show the carbon and oxygen contents are 90.57 and 9.43 respectively. The reduction process was done at temperature of 150oC and 250oC. The result after reduction show the composition carbon increased 2.43% by arising the temperature. The increasing carbon with temperature can be considered due to the broken bond the CO molecule. The dissociation CO reaction can be considered due to the oxygen atom bind to hydrogen.